PENINGKATAN KESEJAHTERAAN MASYARAKAT MELALUI PENGEMBANGAN INFRASTRUKTUR DAN PENANDA WISATA DI DESA SALUMBIA - Riski Nurhazizah; Arlin S Naukoko; Sudirman La Tjemma; Ilmuddin Ilmuddin; Ika Wahyuni Putri; Dwi Utami Putri (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to revitalize the potential of the red shrimp tourist attraction in Salumbia Village, which has experienced a significant decline in visitors due to a lack of promotion and supporting facilities or infrastructure. Adopting a participatory approach, the program focuses on improving community welfare by developing comprehensive infrastructure and tourist signage. Implementation methods included field surveys to identify urgent needs, community workshops to design signs and facilities, and the construction of new infrastructure, such as access bridges and rest areas. The results of this activity demonstrated a significant increase in the destination's attractiveness, reflected in increased visits and local economic activity. The newly designed signage serves not only as a directional sign but also as an educational and promotional tool, reinforcing Salumbia Village's identity as a red shrimp tourist destination. The program concludes that community-based tourism revitalization, supported by appropriate infrastructure interventions, can be an effective strategy for improving economic well-being, environmental sustainability, and strengthening community ownership of a place's local potential.